HUBUNGAN PENDIDIKAN KARAKTER DENGAN KECERDASAN EMOSIONAL SISWA DI SEKOLAH SMA NEGERI 4 BANGKO PUSAKO KABUPATEN ROKAN HILIR - Tika Tika; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the relationship between character education and emotional intelligence of students in SMA Negeri 4 Bangko Pusako. The formulation of the problem in this study is "How is the Relationship between Character Education and the Emotional Intelligence of Students in SMA Negeri 4 Bangko Pusako, Rokan Hilir Regency". The purpose of this study was to determine the relationship between character education and emotional intelligence in SMA Negeri 4 Bangko Pusako, Rokan Hilir Regency. The benefits of the research are giving ideas for the development of character education of students in schools that continue to develop according to what has been taught and applied in schools and around them. This research method is descriptive quantitative, the data collection instruments used in this study are questionnaires, observations and interviews which consist of 28 indicators. by 28 questions. The population in this study were students of SMA Negeri 4 Bangko Pusako, the sample used in this study was the proportional sampling technique. Based on the research results, it was found that Character Education has a significant relationship with students' Emotional Intelligence. This means that if the character education is high, the emotional intelligence will be high and vice versa, if the character education of the child is low, the emotional intelligence of the child is also low. This means that character education has an effect of 52.70% on emotional intelligence. Based on the Ha hypothesis test: There is a significant relationship between Character Education and the Emotional Intelligence of Students in SMA Negeri 4 Bangko Pusako, Rokan Hilir Regency. Key Words: Relationship, Character education, Emotional Intelligence